Excessive daytime sleepiness among pregnant women: An epidemiological study. Issue 1 (January 2014) - Nakagome, Sachi; Kaneita, Yoshitaka; Itani, Osamu; Ikeda, Maki; Ichinose, Atsushi; Morioka, Hisayoshi; Osaki, Yoneatsu; Ohida, Takashi
Abstract The aim of the present study was to clarify the prevalence of excessive daytime sleepiness and its associated factors among pregnant women in Japan. Of the 940 randomly selected survey locations identified by the Japan Association of Obstetricians and Gynecologists, 344 obstetric institutions participated in the survey. The study was conducted on women with confirmed pregnancies who had had a second or subsequent consultation at one of these institutions. The survey items included age, highest educational achievement, trimester of pregnancy, number of pregnancies, employment status, smoking, alcohol consumption, restless sleep, difficulty initiating sleep, difficulty maintaining sleep, early morning awakening, sleep duration, napping, snoring or breathlessness, and restless leg syndrome. The Epworth Sleepiness Scale was used to assess the level of excessive daytime sleepiness. We calculated the prevalence of excessive daytime sleepiness and then examined its associated factors using χ2 test and multiple logistic regression analysis. The prevalence of excessive daytime sleepiness among pregnant women was 6.2%. The results of multiple logistic regression analysis indicated that the adjusted odds ratio with regard to excessive daytime sleepiness was significantly higher among younger women and those in an earlier trimester of pregnancy. The odds ratio with regard to excessive daytime sleepiness was also significantly higher for women in their first pregnancy, full‐time workers, and current alcohol consumers. Women indicating the presence of sleep‐related issues, including restless sleep, difficulty maintaining sleep, napping, snoring or breathlessness, and symptoms of restless leg syndrome, reported significantly higher levels of excessive daytime sleepiness.